2011
DOI: 10.5860/lrts.55n4.221
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User-Contributed Metadata's Potential to Enhance Access to Literary Works

Abstract: LRTS 55(4) and tag photographs), or on narrowly-focused, disciplinespecific websites. The research project reported here sought to compare similarities and identify differences in user tags assigned in a social networking site and Library of Congress Subject Headings (LCSH) assigned in a library catalog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…33 Similarly, DeZelar-Tiedman's exploration of works of English and American literature in an academic library and LibraryThing demonstrates that tags work to facilitate access to material. 34 Peterson and McGlinn discuss Hennepin County Library's efforts to create a virtual community of readers. In an attempt to engage users as active participants and to combine staff-and patron-contributed content in an attractive and interactive way, the library created BookSpace (http://www.hclib.org/pub/bookspace/), an online RA Web site that blends traditional staff-produced and subscription-based RA resources with usercontributed content.…”
Section: Literature Reviewmentioning
confidence: 98%
“…33 Similarly, DeZelar-Tiedman's exploration of works of English and American literature in an academic library and LibraryThing demonstrates that tags work to facilitate access to material. 34 Peterson and McGlinn discuss Hennepin County Library's efforts to create a virtual community of readers. In an attempt to engage users as active participants and to combine staff-and patron-contributed content in an attractive and interactive way, the library created BookSpace (http://www.hclib.org/pub/bookspace/), an online RA Web site that blends traditional staff-produced and subscription-based RA resources with usercontributed content.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Once Web 2.0 and social media sites became popular, they attracted the research interest of many scholars and information professionals. Some studies discussed social tags with classic topics, such as information organization (Golub et al , 2014; Tennis, 2006; Wetzker et al , 2008; Yi and Chan, 2009) and information retrieval (Carman et al , 2008; DeZelar-Tiedman, 2011; Gelernter, 2007; Guerra and LaPlante, 2011; Li et al , 2008; Ruiz and Chin, 2010); some investigated the types of tags (Golder and Huberman, 2006; Gupta et al , 2010; Thomas et al , 2009); some focused on tagging behaviour and the motivation behind it; some studies paid attention to the relationship between book tags and controlled vocabularies, such as subject headings or Dublin Core (Catarino and Baptista, 2010), and the application of social tags in library service (DeZelar-Tiedman, 2011; Gelernter, 2007; Kakali and Papatheodorou, 2010; Lu et al , 2010; Peters, 2009; Thomas et al , 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After comparing tags in LibraryThing with subject headings in the Library of Congress, Rolla (2009) concluded that a better means of indexing is to combine social tagging with subject headings. Further studies adopted a similar method and compared social tags in LibraryThing with subject headings in the Library of Congress to control social tagging (Golub et al , 2014; Yi and Chan, 2009) and complement traditional indexing (Bartley, 2009; DeZelar-Tiedman, 2011; Golub et al , 2014; Lawson, 2009; Lu et al , 2010; Thomas et al , 2009; Wu et al , 2013). Some studies on images and comparable materials made similar comparisons between tags and controlled vocabularies (Golbeck et al , 2011; Petek, 2012; Rorissa, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other examples of social technologies include the use of social tagging within the library’s catalog, which allows users to categorize materials based on user-generated keywords. This type of participatory media helps library and information science (LIS) professionals determine how their library users categorize items while also enhancing the subject-specific access to information (Clements and Liew, 2016; DeZelar-Tiedman, 2011). The use of social technologies within the library not only provides a low-cost and highly efficient means of communication between the library and its patrons (Fernandez, 2009), but also provides the ability to market the library in the face of budget cuts, develop community networks and fundraise (Blakeman and Brown, 2010).…”
Section: Introductionmentioning
confidence: 99%